Improving gas component detection of an ultrasonic tomography system for monitoring liquid/gas flow - N. M., Nor Ayob; Sazali, Yaacob, Prof. Dr.; Zulkarnay, Zakaria; Ruzairi, Abd Rahim; M. R., Manan (Institute of Electrical and Electronics Engineers (IEEE), 2010)
Link to publisher's homepage at http://ieeexplore.ieee.org/